EFL Teachers’ TPACK and Their Espoused Use of ICT Based on SAMR Models - Maulana Mualim; Fakhrezy Rizal Maulana (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
Information and Communication Technology (ICT) has been an inseparable part of human life. Its integration into education is very important. This study aims to describe the Technological Pedagogical Content Knowledge (TPACK) of English teachers in Banyumas Regency, their competence in using ICT based on the Substitution, Augmentation, Modification, and Redefinition (SAMR) model; and the influence of their TPACK to their ICT integration capabilities. This research applied a Mixed Method Research with explanatory sequential design. The respondents of the quantitative phase were 31 teachers while the informants of the qualitative phase were 4 teachers taken randomly. Quantitative data were collected through two questionnaires. Meanwhile, Qualitative data were collected through observations, interviews, and documentation. The quantitative data were analyzed using SPSS while the qualitative data were analyzed using the Miles & Huberman model including data reduction, data presentation, and conclusions. The results showed that the teachers’ TPACK was in "good" category with an average score of 2.89 (in the range of 2,5≤x